New taxa, distribution and biological records of Afrotropical Coraebini Bedel, 1921 (Coleoptera: Buprestidae: Agrilinae) - Bellamy, C. L. (Zootaxa, 2008)
One new genus and three new species of southern African Coraebini are proposed. Ethiopoeus gen. nov. is described for Meliboeus croesus Obenberger, 1931, yielding E. croesus, comb. nov. The fifth species of Paradorella, P. natalensis sp. nov. is described from South Africa, Kwazulu-Natal, and diagnosed in a key to the genus. The second known species of Pseudokerremansia, P. zuluensis sp. nov. is described from South Africa, Kwazulu-Natal and contrasted with P. arcuata (Péringuey, 1908). The fifth known species of Strandietta, S. austroafricana sp. nov. is described from Entabeni Forest Reserve in South Africa, with a key to the genus. Additional distribution and host records are given for species of Anodontodora Obenberger, 1931, Asymades Kerremans, 1893, Chalcophlocteis Obenberger, 1924, Discoderoides Théry, 1936, Paradorella Obenberger, 1923 and Strandietta Obenberger, 1931. Lectotypes are designated for Chalcophlocteis hauseri Obenberger, 1931 and Meliboeus croesus Obenberger, 1931.